Alterations in plasma levels of metabolic hormones and energy metabolites in working lactating Murrah buffaloes - SINGH, S V; UPADHYAY, R C (The Indian Journal of Animal Sciences, 2013)
Studies, were conducted on 5 lactating non-pregnant female Murrah buffaloes during summer and winter, to know the effect of season and work on some metaboliles and hormones. The level of NEFAI and lactic acid gradually increased with the duration and intensity of work. Blood glucose did not exhibit a significant change dne 10 work and season. However, after rest of 2-3 hr the blood glucose level returned to pre-work level, whereas NEFA and lactic acid did not return. Plasma thyroxine thyroxine and triodothyronine levels decreased during summer but in winterlevels did not vary much.level of plasma insulin decreased after ploughing lind insulin levels remmed to pre-work levels during rest.